2021
DOI: 10.1038/s41598-021-84320-8
|View full text |Cite
|
Sign up to set email alerts
|

Homologies between SARS-CoV-2 and allergen proteins may direct T cell-mediated heterologous immune responses

Abstract: The outbreak of the new severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a public health emergency. Asthma does not represent a risk factor for COVID-19 in several published cohorts. We hypothesized that the SARS-CoV-2 proteome contains T cell epitopes, which are potentially cross-reactive to allergen epitopes. We aimed at identifying homologous peptide sequences by means of two distinct complementary bioinformatics approaches. Pipeline 1 included prediction of MHC Class I and Class II epitopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…reduced chance on a cytokine storm and hyper-inflammation [ 32 ], and, allergen proteins directing T cell-mediated heterologous immune responses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…reduced chance on a cytokine storm and hyper-inflammation [ 32 ], and, allergen proteins directing T cell-mediated heterologous immune responses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that asthma patients may be more affected by the heterologous immune response against SARS-CoV-2. In asthma patients sensitized to one of the predicted aeroallergens, the similarities with the SARS-CoV-2 proteome may be protective by preventing an overwhelming type 1 response and the accompanying cytokine storm ( 94 ).…”
Section: Asthma and Covid-19mentioning
confidence: 99%
“…These data suggest the third possibility by which the T-cells, recognizing the epitopes, are primed by the exposure to other ubiquitous antigens. A recent report suggested that such sequence homology exists between SARS-CoV-2 peptides and peptides from allergen proteins [71], malaria proteins [72], and antigenic proteins in BCG, OPV, MMR, and some other vaccines [73]. Perhaps sequence homology, in the context of 9-mer T-cell epitopes, between pathogens is more common than what was originally thought.…”
Section: Epitope Cross-reactivity With Human Peptides Human Common Co...mentioning
confidence: 99%